LINGUISTIC FEATURES OF SYMBOLS IN ALISHER NAVOI’S HERITAGE - Shavkatovna, Sharipova Dilnoza; Istamovna, Ibatova Nargiz; Zoirovna, Narzieva Inobat (International Journal of Psychosocial Rehabilitation, 2020)
Studying the lyrical heritage of Alisher Navoi up to the twentieth century, the great representative of Turkish literature, the greatest Turkish poet, Alisher Navoi is a thinker who united the Turkish people from “China to Huroson” under one literary flag. Alisher Navoi, as a great word artist, has taken Turkish art to a world of both meaning and form. Therefore, with the centuries gone by, the spiritual need for its literary heritage is growing. This is further evidence of the truthfulness of the following prophetic thoughts expressed by the great poet in his talk in the “Muhokamat-ul-Lughatayn”: “Umidim uldur va xayolimg’a andoq kelurkim, so’zim martabasi avjdin quyi inmag’ay va bu tartibim kavkabasia’lo darajadin o’zga yerni beganmagay”. Studying the life and works of Alisher Navoi began in the life of the poet. Abdurahman Jami was the first to initiate this noble cause. However, Navoi has always been interested in learning the rich literary heritage of his country.